RESPONS SISWA TERHADAP MEDIA PEMBELAJARAN BERBANTUAN POWTOON PADA PEMBELAJARAN TEKS NEGOSIASI SISWA KELAS X - Putri Fiqriani Nurromdon; Indra Permana; Yusep Ahmadi F (Parole : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2023)
This research article aims to determine students' responses to powtoon learning media, and to determine the ability to write negotiating texts with powtoon-assisted learning media. The method used in this study is descriptive qualitative method with data collection techniques using questionnaires and tests. Learning is done with the Discovery Learning learning model. Based on the results of the study, it was shown that student responses obtained an average percentage of 84.53%, it can be concluded that the use of instructional media has received a good enough response to be used in learning, and from the results of the recapitulation of knowledge and skills tests the average value of knowledge and students' skills after using learning media is 91.6%. Thus it is stated that the students' abilities in understanding and writing negotiating texts are categorized very well. Based on the results of the discussion, it was concluded that powtoon learning media can be used in the process of learning activities, especially in learning negotiating text for class X high school students. Powtoon-assisted learning media is also effective in the role of increasing learning motivation and especially in the results of writing skills